Inflammatory Mediators in Oral Cancer: Pathogenic Mechanisms and Diagnostic Potential - Niklander, Sven E. (Frontiers in Oral Health, 2021)
Approximately 15% of cancers are attributable to the inflammatory process and growing evidence supports an association between oral squamous cell carcinoma (OSCC) and chronic inflammation. Different oral inflammatory conditions, such as oral lichen planus (OLP), submucous fibrosis and oral discoid lupus are all predisposing for the development of OSCC. The microenvironment of this conditions contains various transcription factors and inflammatory mediators with the ability to induce proliferation, epithelial-to-mesenchymal transition (EMT) and invasion of genetically predisposed lesions, thereby promoting tumor development. In this review, we will focus on the main inflammatory molecules and transcription factors activated in OSCC, with emphasis on their translational potential.